A Discrete Cobalt Complex Obtained from a 1 D Coordination Polymer for Highly Selective Sensing of the Mercury(II) Ion. Issue 7 (26th May 2014) - Mishra, Anurag; Jo, Jae‐Ho; Kim, Hyunuk; Woo, Sangkook; Chi, Ki‐Whan
Abstract: A unique structural transformation in a 1 D chain coordination network 2 is converted to a discrete compound 3 accompanied by a change in the ion‐exchange system. Remarkably, 3 produced a turn‐on fluorescence and selective sensing for Hg 2+, whereas other ions, such as K +, Mg 2+, Ca 2+, Mn 2+, Fe 2+, Co 2+, Ni 2+, Cu 2+, Zn 2+, and Cd 2+, did not show any notable effects. Thus, the Hg 2+ ‐selective fluorescent chemosensor was free from interference by competing metal ions. Abstract : A sensitive issue : A discrete ethynyl pyridine amide‐based cobalt complex shows an enhanced fluorescence signal with high sensitivity and selectivity for Hg 2+ ions relative to other metal ions (see figure). Selective chelation of Hg 2+ with the complex occurs through the coordination of the nitrogen atoms of the ethynyl pyridine moieties.